Advancing children's rights in detention: a model for international reform - Kilkelly, Ursula (Bristol University Press, 2022)
Drawing on Ireland's experience of transforming law, policy and practice and combining theory with real-life experiences, this compelling book demonstrates how a progressive rights-based approach to child detention can be implemented. The UN Global Study on Children Deprived of Liberty detailed many children's poor experiences in detention, highlighting the urgent need for reform. Applying a child-centred model of detention that fulfils the rights of the child under the five themes of Provision, Protection, Participation, Preparation and Partnership, this original book illustrates how reform can happen. Drawing on Ireland's experience of transforming law, policy and practice and combining theory with real-life experiences, this compelling book demonstrates how children's rights can be implemented in detention. This important case study of reform presents a powerful argument for a progressive, rights-based approach to child detention. Worthy of international application, the book shares practical insights into how theory can be translated into practice